Pregnancy and Neonatal Outcomes in SARS-CoV-2 Infection: A Systematic Review - Reem S. Chamseddine; Farah Wahbeh; Frank Chervenak; Laurent J. Salomon; Baderledeen Ahmed; Arash Rafii (Hindawi Limited, 2020)
With the emergence of SARS-CoV-2 and its rapid spread, concerns regarding its effects on pregnancy outcomes have been growing. We reviewed 245 pregnancies complicated by maternal SARS-CoV-2 infection across 48 studies listed on PubMed and MedRxiv. The most common clinical presentations were fever (55.9%), cough (36.3%), fatigue (11.4%), and dyspnea (12.7%). Only 4.1% of patients developed respiratory distress. Of all patients, 89.0% delivered via cesarean section (n=201), with a 33.3% rate of gestational complications, a 35.3% rate of preterm delivery, and a concerning 2.5% rate of stillbirth delivery or neonatal death. Among those tested, 6.45% of newborns were reported positive for SARS-CoV-2 infection. Relative to known viral infections, the prognosis for pregnant women with SARS-CoV-2 is good, even in the absence of specific antiviral treatment. However, neonates and acute patients, especially those with gestational or preexisting comorbidities, must be actively managed to prevent the severe outcomes being increasingly reported in the literature.